Controlled clinical laboratory comparison of BACTEC plus aerobic/F resin medium with BacT/Alert aerobic FAN medium for detection of bacteremia and fungemia. - Jorgensen, J H (1997)
Blood specimens collected from adult patients with suspected sepsis in four medical centers were inoculated into BACTEC Plus/F and BacT/Alert FAN aerobic culture bottles. Both bottles of 7,401 bottle pairs contained the prescribed blood volume of 8 to 12 ml. Bottles were incubated in their respective instruments for a standard 7-day protocol or until the instruments signaled that they were positive. A total of 720 isolates that were judged to represent true infections were recovered from 338 patients; 451 isolates were recovered from both bottles, 143 were recovered from only the Plus/F bottle, and 126 were recovered from only the FAN bottle (P was not significant). Although more Histoplasma capsulatum isolates were recovered from Plus/F bottles (P < 0.005), there were no other statistically significant differences in recovery rates of individual species or groups of organisms between the two systems. Of 329 monomicrobic patient septic episodes, 244 episodes were detected by both blood culture systems, 40 were detected only by the BACTEC system, and 45 were detected only by the BacT/Alert system (P was not significant). There was no significant difference between the two systems in the detection of septic episodes among patients receiving antibiotic therapy at the time of blood cultures. Of the cultures found to be positive within the first 72 h of incubation, detection was on average earlier by the BACTEC system (16.9 h) than by the BacT/Alert system (18.7 h). Larger differences in average time to detection were seen with streptococci (10.7 h by the BACTEC system and 17.9 h by the BacT/Alert system) and yeasts (an average of 29.4 h by the BacT/Alert system versus 37.2 h by the BACTEC system). With the exception of the differences noted above, BACTEC Plus/F aerobic resin and BacT/Alert aerobic FAN blood culture bottles were comparable in their abilities to recover aerobic and facultative organisms.